Secure Wireless Sensor Network using Cryptography for Smart Farming Systems - Wahid, Abdul; Juliady, Ilham; Zain, Satria Gunawan; Parenreng, Jumadi Mabe (Internet of Things and Artificial Intelligence Journal, 2022)
Internet of Things (IoT) technology has become part of human life. Agriculture in many parts is one of IoT implementation segment including the Cultivation of mold oysters. Internet of Things (IoT) is applied to collect data from combined sensors in the Wireless Sensor Network (WSN) will make it easy for farmers to monitor and control garden they remotely. Regardless of the application system control distance far based WSN that will make it easy for a farmer, the system has gap security, and one of them that is hacking and tapping of communication data The IoT . is really dangerous on effort if condition room mold oyster the known by someone hacker who can just is rival effort. It is a needed something method for secure communication when the data transfer process is over-guaranteed. The method used is application Base64 -based data encryption/decryption on WSN node devices and controlling and monitoring mobile devices. Based on results trials carried out after the implementation of Secure WSN with scenario tapping using the Wireshark tool show no data can be read. Analysis results show that this model could be applied as Secure WSN for Smart Farming System.